Застосування методів нечіткої векторної оптимізації для складання дієти - Мірошниченко, О. О. (ХНУРЕ, 2023)
The work is devoted to the compilation of a human diet that would provide a person's daily need for essential nutrients, correspond to the financial capabilities of a person and have adequate weight and volume. The initial data for the task is the composition of the products used, the content of useful substances in them, calorie content and cost. To solve the problem, fuzzy vector optimization methods are used. The goal in this problem is not clearly defined. To solve this problem, we use the idea of Zade – Bellman, according to which the fuzzy solution of the problem under consideration is the intersection of a fuzzy goal and a fuzzy set of alternatives.
Keywords: складання раціону; нечітка векторна оптимізація; нечітка множина альтернатив; ідея Заде-Беллмана